Small female rib cage fracture in frontal sled tests. (2nd January 2017) - Shaw, Greg; Lessley, David; Ash, Joseph; Poplin, Jerry; McMurry, Tim; Sochor, Mark; Crandall, Jeff
ABSTRACT: Objectives: The 2 objectives of this study are to (1) examine the rib and sternal fractures sustained by small stature elderly females in simulated frontal crashes and (2) determine how the findings are characterized by prior knowledge and field data. Methods: A test series was conducted to evaluate the response of 5 elderly (average age 76 years) female postmortem human subjects (PMHS), similar in mass and size to a 5th percentile female, in 30 km/h frontal sled tests. The subjects were restrained on a rigid planar seat by bilateral rigid knee bolsters, pelvic blocks, and a custom force-limited 3-point shoulder and lap belt. Posttest subject injury assessment included identifying rib cage fractures by means of a radiologist read of a posttest computed tomography (CT) and an autopsy. The data from a motion capture camera system were processed to provide chest deflection, defined as the movement of the sternum relative to the spine at the level of T8.  A complementary field data investigation involved querying the NASS-CDS database over the years 1997–2012. The targeted cases involved belted front seat small female passenger vehicle occupants over 40 years old who were injured in 25 to 35 km/h delta-V frontal crashes (11 to 1 o'clock). Results: Peak upper shoulder belt tension averaged 1, 970 N (SD = 140 N) in the sled tests. For all subjects, the peak x -axis deflection was recorded at the sternum with an average of −44.5 mm or 25% of chest depth. The thoracic injury severity based on the number and distribution of rib fractures yielded 4 subjects coded as Abbreviated Injury Scale (AIS) 3 (serious) and one as AIS 5 (critical). The NASS-CDS field data investigation of small females identified 205 occupants who met the search criteria. Rib fractures were reported for 2.7% of the female occupants. Conclusions: The small elderly test subjects sustained a higher number of rib cage fractures than expected in what was intended to be a minimally injurious frontal crash test condition. Neither field studies nor prior laboratory frontal sled tests conducted with 50th percentile male PMHS predicted the injury severity observed. Although this was a limited study, the results justify further exploration of the risk of rib cage injury for small elderly female occupants.